Fusaresters A–E, new γ-pyrone-containing polyketides from fungus Fusarium sp. Hungcl and structure revision of fusariumin D. Issue 22 (1st May 2019) - Gong, Jiaojiao; Chen, Chunmei; Mo, Shuyuan; Liu, Junjun; Wang, Wenjing; Zang, Yi; Li, Huaqiang; Chai, Chenwei; Zhu, Hucheng; Hu, Zhengxi; Wang, Jianping; Zhang, Yonghui
Abstract : Chemical investigation of a marine-derived fungus Fusarium sp. Hungcl afforded five new γ-pyrone-containing polyketides, fusaresters A–E. Abstract : Marine-derived fungi have been regarded as an under-explored and promising reservoir of structurally novel and bioactive natural products. In this study, five new γ-pyrone-containing polyketides, fusaresters A–E (1–5 ), were isolated and identified from the culture extracts of a marine-derived fungus Fusarium sp. Hungcl. The structures of compounds1–5 were elucidated on the basis of their HRESIMS and NMR spectroscopic data as well as 13 C NMR calculation and electronic circular dichroism (ECD) analyses. Remarkably, the structure of fusariumin D was revised to (9 S *, 11 S *)-3 . All these isolates were tested for the cytotoxicity against seven human cancer cell lines, including SW480, HL-60, A549, MCF-7, HepG2, HeLa and SMMC-7721, and the inhibitory activity against protein tyrosine phosphatase 1B (PTP1B). The results revealed that only compound2 showed a weak inhibition rate of 56% at 40 μM.